2019
DOI: 10.2106/jbjs.19.00568
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Diagnosis of Ipsilateral Femoral Neck and Shaft Fractures

Abstract: Background: Despite increased awareness of ipsilateral femoral neck fractures in patients with high-energy femoral shaft fractures and advanced imaging with thin-cut high-resolution computed tomography (CT), failure of diagnosis remains problematic. The purpose of the present study was to determine if the preoperative diagnosis of ipsilateral femoral neck fractures in patients with high-energy femoral shaft fractures can be improved with magnetic resonance imaging (MRI) compared with radiographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Objective sound waves can also be used as a diagnostic test or screening tool in the assessment of occult hip fractures [22]. Moreover, a recent study found that rapid limited-sequence pelvis MRI for patients with femoral shaft fractures could identify femoral neck fractures that were not diagnosed on thin-cut high-resolution CT [23]. In our present series, nine of the patients were young males (64.2%), two had open femoral shaft fractures (14.3%), seven had multisystem injuries (50.0%), and two had ipsilateral knee injuries (14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Objective sound waves can also be used as a diagnostic test or screening tool in the assessment of occult hip fractures [22]. Moreover, a recent study found that rapid limited-sequence pelvis MRI for patients with femoral shaft fractures could identify femoral neck fractures that were not diagnosed on thin-cut high-resolution CT [23]. In our present series, nine of the patients were young males (64.2%), two had open femoral shaft fractures (14.3%), seven had multisystem injuries (50.0%), and two had ipsilateral knee injuries (14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Objective sound waves can also be used as a diagnostic test or screening tool in the assessment of occult hip fractures [22]. Moreover, a recent study found that rapid limitedsequence pelvis MRI for patients with femoral shaft fractures could identify femoral neck fractures that were not diagnosed on thin-cut high-resolution CT [23]. In our present series, nine of the patients were young males (64.2%), two had open femoral shaft fractures (14.3%), seven had multisystem injuries (50.0%), and two had ipsilateral knee injuries (14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Objective sound waves can also be used as a diagnostic test or screening tool in the assessment of occult hip fractures [22]. Moreover, a recent study found that rapid limited-sequence pelvis MRI for patients with femoral shaft fractures could identify femoral neck fractures that were not diagnosed on thin-cut highresolution CT [23]. In our present series, nine of the patients were young males (64.2%), two had open femoral shaft fractures (14.3%), seven had multisystem injuries (50.0%), and two had ipsilateral knee injuries (14.3%).…”
Section: Discussionmentioning
confidence: 99%